Evaluation of in-stent stenosis by magnetic resonance phase-velocity mapping in nickel-titanium stents - Holton, Andrea D.; Walsh, Edward G.; Anayiotos, Andreas (My University, 2005)
Purpose: To evaluate different grades of in-stent stenosis in a nickel-titanium stent with MRI. Materials and Methods: Magnetic resonance phase velocity mapping (MR-PVM) was used to measure flow velocity through a 9-mm NiTi stent with three different degrees of stenosis in a phantom study. The tested stenotic geometries were 1) axisymmetric 75%. 2) axisymmetric 90%, and 3) asymmetric 50%. The MR-PVM data were subsequently compared with the velocities from computational fluid dynamic (CFD) simulations of identical conditions. Results: Good quantitative agreement in velocity distribution for the 50% and 75% stenoses was observed. The agreement was poor for the 90% stenosis, most likely due to turbulence and the high-velocity gradients found in the small luminal area relative to the pixel resolution in our imaging settings. Conclusion: The accuracy of the MRI velocities inside the stented area renders MRI a modality that may be used to assess moderate to severe in-stent restenosis (ISR) in medium-sized vascular stents in peripheral vessels, such as the iliac, carotid, and femoral arteries. Advances in MR instrumentation may provide sufficient resolution to obtain adequate velocity information from smaller vessels, such as the coronary arteries, and allow MRI to substitute for invasive and expensive catheterization procedures currently in clinical use.
Keywords: Hemodynamics; Titanium; Nickel; Carotid artery; Geometry